Comparison of the Effectiveness of Mentalization-Based Therapy and Unified Transdiagnostic Treatment on the Sexual Schemas of Religiously Committed Women Who Have Experienced Infidelity - Bengari, Afsaneh; Yousefi, Emad; khajehpour, Leila (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The objective of this study was to compare the effectiveness of Mentalization-Based Therapy (MBT) and Unified Transdiagnostic Treatment (UTT) on the sexual schemas of religiously committed women who have experienced infidelity.Methods and Materials: This study employed a quasi-experimental design featuring a pre-test and post-test with a control group. The sample consisted of 45 religiously committed women who had experienced spousal infidelity, diagnosed by psychologists at counseling centers in Shiraz. Participants were selected through convenience sampling and randomly assigned to three groups of 15: a control group, an MBT group, and a UTT group. The intervention groups received respective therapy sessions, while the control group received no intervention. Data were collected using the Women's Sexual Self-Schema Questionnaire by Anderson and Cyranowski (1994). Data analysis was performed using Multivariate Analysis of Covariance (MANCOVA).Findings: The results of the MANCOVA indicated that there were no significant differences in the post-test mean scores of sexual schemas among the control group, MBT group, and UTT group (p > .05). Thus, neither therapeutic approach had a significant impact on the sexual schemas of the participants.Conclusion: The study concluded that both Mentalization-Based Therapy and Unified Transdiagnostic Treatment were ineffective in altering the sexual schemas of religiously committed women who had experienced infidelity. The findings suggest that these therapeutic methods may not address the deep-rooted cognitive and experiential structures underlying sexual schemas.